Sangmotivets funktion i to tekstrettelser hos Grundtvig - Schiøler, Aage (Grundtvig-studier, 2007)
Sangmotivets funktion i to tekstrettelser hos Grundtvig [The function of the song-motif in two of Grundtvig ’s emendations]By Aage Schiøler With reference to three typical examples of Grundtvig’s use of the song-motif as his means of indicating a turning point and an intervention in human existence effected by the external agency named God and of describing the contents thereof as a paradigm, the article analyses the background of two emendations among the many Grundtvig made when republishing his works. In the first example, the compound motive for the emendation is seen to be a combination of the shift in the popular attitude towards his views on the general status of the Danish Church, especially his avid interest in renewing the official hymn book, and the shift from a personal to a communal mode in the poet’s approach to the text (marked by the use of some stanzas from the original poem as a church hymn). The second example, involving a change from a Christmas setting to a reference to the Eucharist (both being viewed as expressions of the incarnation), is seen as an attempt to avoid potential misunderstanding of his perception of incarnation as a dynamic, historically integrated event - misunderstanding resulting from concentration upon the familyoriented, seasonally determined Yule-celebration instead of the geographically and chronologically all-inclusive purpose of the sacrament. In both cases, the emendation can be seen as a reaction within the field of public communication.